INVESTMENT PLATFORMS EVOLUTIONS – ETF FUNDS - Kraiński, Karol (Copernican Journal of Finance & Accounting, 2017)
Investment platforms, despite the short length of service on the Polish market, subject to continuous development. The nucleus of the creation of this product were the umbrella investment funds. They allowed free passage between funds without additional costs and too complicated formalities. This form, however, proved insufficient for the participants, because such diversification is just a hoax. Of course, one of the factors that contributed positively to the development of platforms were changes in the pension system. Platform initiated a kind of a new chapter in the operation of investment funds allow participants to freely switch between funds of different companies, often with different investment profile and risk, without at the same time leaving the product as a whole. Unfortunately, among the platform they appeared non-creditable charge liquidation, which largely borne by the participants. The main factor that forced changes in Poland, became the lawsuits, mainly on the Insurance of Investment Platform based on Insurance Capital Funds. The first adverse judgment in this case concerned the AEGON Insurance Group, while another case is in progress. A string of these events resulted in a new direction of development platforms, namely, basing their actions on the Fun-souls ETF. This link aims to reduce the fees incurred by the participants, but mainly to increase the rates of return obtained. In this connection, it is worth a closer look at this solution. The purpose of this article is to present the first ETF investment platform in Poland.